The access manual designing, auditing and managing inclusive built environments - Sawyer, Ann; Bright, Keith (John Wiley and Sons, Ltd, 2014)
This manual covers the design, improvement, maintenance and management of accessible environments. It shows you how to provide and run buildings, services, and employment facilities to enable independent and convenient use by everyone.